Paratyphoid fever: Splicing the global analyses - Teh, C.S.J.; Chua, K.H.; Thong, Kwai Lin (International Journal of Medical Sciences, 2014)
The incidence of enteric fever caused by Salmonella enterica serovar Paratyphi A (S. Paratyphi A) is increasing in many parts of the world. Although there is no major outbreak of paratyphoid fever in recent years, S. Paratyphi A infection still remains a public health problem in many tropical countries. Therefore, surveillance studies play an important role in monitoring infections and the emergence of multidrug resistance, especially in endemic countries such as India, Nepal, Pakistan and China. In China, enteric fever was caused predominantly by S. Paratyphi A rather than by Salmonella enterica serovar Typhi (S. Typhi). Sometimes, S. Paratyphi A infection can evolve into a carrier state which increases the risk of transmission for travellers. Hence, paratyphoid fever is usually classified as a “travel-associated” disease. To date, diagnosis of paratyphoid fever based on the clinical presentation is not satisfactory as it resembles other febrile illnesses, and could not be distinguished from S. Typhi infection. With the availability of Whole Genome Sequencing technology, the genomes of S. Paratyphi A could be studied in-depth and more specific targets for detection will be revealed. Hence, detection of S. Paratyphi A with Polymerase Chain Reaction (PCR) method appears to be a more reliable approach compared to the Widal test. On the other hand, due to increasing incidence of S. Paratyphi A infections worldwide, the need to produce a paratyphoid vaccine is essential and urgent. Hence various vaccine projects that involve clinical trials have been carried out. Overall, this review provides the insights of S. Paratyphi A, including the bacteriology, epidemiology, management and antibiotic susceptibility, diagnoses and vaccine development.